Pengaruh Promosi Menggunakan Iklan Media Cetak dan Sosial Media terhadap Minat Wisatawan Tubing River - Enggi Rahmad Syahputra; Subandrio Rahmad Subandrio (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of promotion using print media advertisements and social media on the interest of visiting tourists in the Tubing River, Permu Bawah Village, Kepahiang Regency. Sampling using purposive sampling technique based on predetermined criteria totaling 110 respondents. Data collection techniques using observation, documentation and questionnaires by testing the instrument validity, reliability, classical assumptions and multiple linear analysis. The processed data was analyzed using the SPSS 25 formula. Based on the results of the study, the significant value for the effect of X1 and X2 together on Y was 0.00. It is known that the Fcount value is 15,539 and the Ftable value is 3.93, so that the Fcount value is (15,539) > Ftable (3.93) with a significant value of 0.00 > 0.05 then, H0 is rejected and H3 is accepted. From the results of the study it can be concluded that print media advertisements and social media together have a significant effect on Interest in Tubing River Tourists in Permu Bawah Village, Kepahiang Regency. Keywords: Print Media Advertising, Tourist Interests, Social Media